Additional species Tylophora tengii Tsiang (Asclepiadaceae R. Br.) for the flora of Vietnam - Bach, Tran The (Academia Journal of Biology, 2015)
Additional species Tylophora tengii Tsiang (Asclepiadaceae R. Br.) for the flora of Vietnam